Pengaruh Motivasi, Budaya Organisasi dan Disiplin terhadap Kinerja Karyawan pada PT. Ardisal Jasa Utama - Endang Hutabarat; Milda Handayani; Rini Wijayaningsih; Tyna Yunita; Hasanuddin Hasanuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of Motivation, Organizational Culture and Discipline on Employee Performance at PT Ardisal Jasa Utama. The type of research used in this research is Quantitative Research. The sampling technique in this research was a saturated sample, namely 57 respondents. The data processing tool used in this research is SPSS software version 26. Based on the results of the research, it shows that motivation variables have a significant effect on the performance of PT. Ardisal Jasa Utama employees, organizational culture variables have a significant effect on the performance of PT.Ardisal Jasa Utama employees, discipline variables have an effect significant impact on the performance of PT Ardisal Jasa Utama employees. The research results also show that the variables of motivation, organizational culture and discipline simultaneously have a positive and significant effect on the performance of PT Ardisal Jasa Utama employees.